Case report and literature review: clinical manifestations and treatment of human RelA deficiency - Wang, Chenghao; Wang, Wenjie; Hui, Xiaoying; Hou, Jia; Zhou, Qinhua; Li, Qifan; Wu, Qi; Ni, Qi; Wu, Bingbing; Sun, Jinqiao; Wang, Xiaochuan (Frontiers in Immunology, 2025)
RelA deficiency resulting from mutations in the human RELA gene is a recently identified inborn errors of immunity (IEI). The RELA gene encodes the RelA (p65) protein, one of the five transcription factors of the NF-κB family, which plays a critical role in the regulation of transcriptional programs essential for the development and maintenance of the immune system, skeletal system, and epithelial tissues. RelA deficiency is classified as RelA haploinsufficiency and RelA dominant-negative. The mainly pathogenesis is that impaired NF-κB activation in fibroblasts, which leads to the downregulation of NF-κB-dependent antiapoptotic protein expression and cytokine transcription, renders fibroblasts susceptible to TNF-induced apoptosis. Clinical manifestations of RelA deficiency are typically characterized by recurrent oral ulcers or Behçet’s disease-like manifestations. Since the first report in 2016, only a few dozen cases of RelA deficiency have been documented worldwide. Treatment strategies have not been standardized, with current mainstream approaches primarily involving immunosuppressive therapies, including TNF inhibitors or glucocorticoids. In this study, we report the clinical phenotypes of three patients with RelA deficiency from two families, along with one novel pathogenic mutation (c.1166_1184del, p.Q389fs) in the RELA gene. This expands the spectrum of pathogenic mutations associated with the RELA gene and clinical manifestations of RelA deficiency. Additionally, we provide a comprehensive summary of the genetic phenotypes, clinical characteristics, and treatment strategies of all previously reported cases of RelA deficiency. Our aim is to increase awareness of this rare IEI and to offer insights that may guide its treatment.